Descripción de la ingesta de alimentos y nutrientes en niños expuestos y no expuestos al programa de complementación alimentaria MANA Infantil en el municipio de Envigado, Colombia, 2006-2010 (2013)
ABSTRATC: MANA is a food complementary program provided to children in Envigado, Antioquia-Colombia. However, there is not information related with the actual food and nutrients intakes of MANA beneficiaries. Objective: To compare food and nutrient intakes between exposed and unexposed of MANA. Methods: Cross sectional study which included 49 exposed and 35 of MANA. Food and nutrient intakes were evaluated by 24 h recall. Results: Complementary food intake was not different between groups (32.5% in exposed and 22.9% in unexposed; p=0.462), general food, energy and nutrients intakes were not different between groups (2.177 kcal/d MANA exposed and 2.037 kcal/d unexposed, p=0.627; 60.2 g protein/d MANA exposed 60.7 g/d unexposed; p=0.640). Macronutrient distribution was balanced in both groups; however, simple carbohydrates (15.5% MANA exposed and 12.7% unexposed; p=0.264), and saturated fatty acid intakes (12.8% MANA exposed and 12.9% unexposed; p=0.608) were higher than the recommended dietary intakes. MANA did not provide micronutrient goals. Conclusion: The achievements of MANA Program were limited, due to a low consumption of food provided.